2019
DOI: 10.47104/ebnrojs3.v1i3.83
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Health Hazards among Oncology Nurses and its Possible Relation to Malpractice and Workplace Environment

Abstract: Context: Chemotherapeutic drugs are chemical substances used for cancer treatment and known to be carcinogenic, teratogenic, and mutagenic to humans. Occupational exposure to chemotherapeutic drugs has led to higher health hazards among nurses who handle them. Aim: Assess chemotherapy health hazards among oncology nurses and its possible relation to malpractice and workplace environment. Method: A descriptive and exploratory research design used in the present study. All available nurses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The third factor that indicates nurses’ non-compliance with safety standards is their performance with antineoplastic drugs. Gamal et al [ 20 ] found that nurses had poor performance in this area and did not follow international standards properly. In Zayed et al [ 14 ] study, two-thirds of nurses’ knowledge about the safe use of antineoplastic drugs was reported to be satisfactory, but only 36.4% of nurses had an appropriate performance.…”
Section: Introductionmentioning
confidence: 99%
“…The third factor that indicates nurses’ non-compliance with safety standards is their performance with antineoplastic drugs. Gamal et al [ 20 ] found that nurses had poor performance in this area and did not follow international standards properly. In Zayed et al [ 14 ] study, two-thirds of nurses’ knowledge about the safe use of antineoplastic drugs was reported to be satisfactory, but only 36.4% of nurses had an appropriate performance.…”
Section: Introductionmentioning
confidence: 99%
“…The third factor that indicates nurses' non-compliance with safety standards is their performance with antineoplastic drugs. Gamal et al (2019) found that nurses had poor performance in this area and did not follow international standards properly [19]. In Zayed et al ( 2019) study, two-thirds of nurses' knowledge about the safe use of antineoplastic drugs was reported to be satisfactory, but only 36.4% of nurses had an appropriate performance.…”
Section: Introductionmentioning
confidence: 99%